Short term outcome comparing conservative and surgical treatment among adolescent idiopathic scoliosis patient - Saiful Azlan Kamisan (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Adolescent idiopathic scoliosis (AIS) defined as a complex three-dimensional spinal column deformity. The treatment option is observational and surgery. Surgery was offered to patients with likelihood of progression with cobbs angle of more than 40-50 degrees. Scoliosis surgery is a high-risk surgery with possible neurological injury, however it is the treatment of choice for patients with a large curve which has been proven to be successful over the years. Therefore, this study objective is to evaluate short term outcome of the quality of life and functional outcome amongst scoliosis patient whom had undergone surgical correction compared to an observational group by using Scoliosis Research Society-30 Patient Questionnaire (SRS-30). This is a cross-sectional study involving 82 patients with 40 patients in the observational group and 42 patients who were operated within the last 10 years with a minimum of follow up of one year. We compared pre and post-operative Cobb's angle and at the last visit, patients completed the SRS-30 questionnaire. We compared the SRS-30 score between the observational group and surgery group, and evaluated the correlation between the radiographic measure and SRS-30 score. There were 79 females and 3 male patients. Forty-seven (57.3%) were Malay, thirty-three (40.2%) were Chinese and two (2.4%) were Indian. Majority of patients (48 patients, 58.5%) were Lenke's type 1 curve. Mean pre-operative Cobb's angle was 54.21 degrees and post-operative Cobb's angle was 14.88 degree. Curve correction improve significantly after surgery (P<0.001). The total SRS-30 overall score for the surgical group was higher compared to the observational group with self-image and appearance score were statistically significant (P<0.001). Curve correction however was statistically not significant in relation to SRS-30 scores. In conclusion, AIS patient who were treated surgically has higher SRS-30 score compared to the observational group. Self-Image and appearance were the most significant factor in a patient's perspective. Although the amount of curve correction did not statistically correlated with the SRS-30 score after the operation, it does however related to the clinical appearance of the patient. Hence, we can conclude that surgical outcome is significantly related to better self-image and appearance, hence a better SRS score. observational and surgery. Surgery was offered to patients with likelihood of progression with cobbs angle of more than 40-50 degrees. Scoliosis surgery is a high-risk surgery with possible neurological injury, however it is the treatment of choice for patients with a large curve which has been proven to be successful over the years. Therefore, this study objective is to evaluate short term outcome of the quality of life and functional outcome amongst scoliosis patient whom had undergone surgical correction compared to an observational group by using Scoliosis Research Society-30 Patient Questionnaire (SRS-30). This is a cross-sectional study involving 82 patients with 40 patients in the observational group and 42 patients who were operated within the last 10 years with a minimum of follow up of one year. We compared pre and post-operative Cobb's angle and at the last visit, patients completed the SRS-30 questionnaire. We compared the SRS-30 score between the observational group and surgery group, and evaluated the correlation between the radiographic measure and SRS-30 score. There were 79 females and 3 male patients. Forty-seven (57.3%) were Malay, thirty-three (40.2%) were Chinese and two (2.4%) were Indian. Majority of patients (48 patients, 58.5%) were Lenke's type 1 curve. Mean pre-operative Cobb's angle was 54.21 degrees and post-operative Cobb's angle was 14.88 degree. Curve correction improve significantly after surgery (P<0.001). The total SRS-30 overall score for the surgical group was higher compared to the observational group with self-image and appearance score were